2020
DOI: 10.1155/2020/7210547
|View full text |Cite
|
Sign up to set email alerts
|

Feature Analysis on Mixed Traffic Flow of Manually Driven and Autonomous Vehicles Based on Cellular Automata

Abstract: This paper attempts to disclose the features of the mixed traffic flow of manually driven vehicles (MVs) and autonomous vehicles (AVs). Considering dynamic headway, the mixed traffic flow was modelled based on the improved single-land cellular automata (CA) traffic flow model (DHD) proposed by Zhang Ningxi. The established CA model was adopted to obtain the maximum flow of the mixed traffic flow and was analyzed under different proportions of AVs. On this basis, the features of the mixed traffic flow were summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Their results showed that the critical vehicle density and the maximum average flow would increase significantly when the ratio of Avs to HVs increases. Hu et al [52] modeled mixed traffic based on an improved single-lane CA model that considered the dynamic headway and explored mixed traffic characteristics under different AV proportions. Considering the difference between CAVs, Avs, and HVs, Vranken et al [53] introduced a new CA model for single lane highways and set the timestep to 0.1 s to improve the model accuracy.…”
Section: Cellular Automata Model In Traffic Simulationmentioning
confidence: 99%
“…Their results showed that the critical vehicle density and the maximum average flow would increase significantly when the ratio of Avs to HVs increases. Hu et al [52] modeled mixed traffic based on an improved single-lane CA model that considered the dynamic headway and explored mixed traffic characteristics under different AV proportions. Considering the difference between CAVs, Avs, and HVs, Vranken et al [53] introduced a new CA model for single lane highways and set the timestep to 0.1 s to improve the model accuracy.…”
Section: Cellular Automata Model In Traffic Simulationmentioning
confidence: 99%
“…Meanwhile, some countries have carried out pilot operations of intelligent connected vehicles [11]. During the development of CAV, the road traffic flow will present a mixed scenario of manually driven vehicles and intelligent networked vehicles, and there are different control measures for the traffic flow operation scenarios under different circumstances [12][13]. Unlike manually driven vehicles, intelligent networked vehicles can realize the information interaction between vehicles and vehicles and between vehicles and roads and other infrastructures with the help of vehicle networking technology [14][15].…”
Section: Introductionmentioning
confidence: 99%
“…With the model’s simplicity, high computational efficiency, and capability to capture the characteristics of real traffic, it is also applied in other complex scenarios like work zone ( 1921 ) and pedestrian flow ( 2224 ). Recently, CA models ( 2531 ) have been used to simulate the heterogeneous traffic of human-driven vehicles and CACC vehicles. Ye and Yamamoto ( 25 ) constructed a CA model for both human driving vehicles and CACC vehicles and evaluated the impact of CACC vehicles on traffic safety.…”
mentioning
confidence: 99%